SAFE POSITIONING FOR NEUROSURGICAL PATIENTS - St. Arnaud, Danielle; Paquin, Marie-Josée (Operating Room Nurses Association of Canada Journal, 2009)
Positioning the patient for surgery is an important part of perioperative nursing care that should not be underemphasized. The combined factors of time, mechanical pressure, and immobility increase the risk of tissue damage. The objectives of perioperative positioning activities are to balance optimal surgical exposure with the prevention of any injury related to position and to maintain normal body alignment without excess flexion, extension, or rotation. After providing general principles of positioning, specific considerations with surgical rationale are presented for each of the commonly used neurosurgical positions (eg. supine, knee-chest, prone, lateral, park-bench, sitting).